Peranan Hukum Adat Dalam Mempertahankan Gastronomi Lokal Sebagai Daya Tarik Wisata Di Desa Sembalun Lombok Timur Nusa Tenggara Barat - Komang Mahawira (JURNAL GASTRONOMI INDONESIA, 2023)
This research uses a qualitative descriptive method with two main focuses: first, on the customary law of the Sembalun village known as "Krama Adat Negeri Sembahulun," and second, on the role of customary law in preserving the local gastronomy of Sembalun village. Data were collected by in-depth interview with the local formal and informal leaders. The research concludes that the customary law in the Sembalun village fulfills the elements of customary law, namely: having a legal structure in the form of "Krama Adat Negeri Sembahulun" having legal substance in the form of established and inherited rules called “awig awig" that impose sanctions for violations, and having a legal culture that is consistently respected and implemented by the community. The customary law of the Sembalun village successfully preserves the local gastronomy, allowing the unique and distinctive Sembalun food and beverages to be enjoyed as a tourism attraction by both domestic and international tourists. The research provides three recommendations: the governments and the community should recognize and protect the customary law of the Sembalun village in accordance with existing regulations, ensuring its continued existence within the community and its ability to preserve the local gastronomy as a tourism attraction in Sembalun village.